In situ study on medium-range order evolution during the polyamorphous phase transition in a Pd-Ni-P nanostructured glass. (20th October 2022) - Fu, Shu; Liu, Sinan; Ge, Jiacheng; Wang, Junjie; Ying, Huiqiang; Wu, Shangshu; Yan, Mengyang; Zhu, Li; Ke, Yubin; Luan, Junhua; Ren, Yang; Zuo, Xiaobing; et al.
Highlights: Bulk-sized nanostructured glasses that exceed millimeters have been prepared. Short-range order structure stably remains before and after laser evaporation. Medium-range order dominates the polyamorphous phase transitions induced by P and T. Multiscale structures and properties can be tailored based on polyamorphism engineering. Abstract: Engineering multiscale structural hierarchies in glassy alloys enable a broad spectrum of potential applications. Metallic glasses were born in hierarchical structures from atomic-to-nanometer scales. However, the frozen-in structures in traditional metallic glasses prepared by rapid quenching techniques are challenging to tailor. Here, we show that a Pd40 Ni40 P20 bulk nanostructured glass of polyamorphous interfacial structures was prepared by inert-gas condensation with a laser evaporation source, and its multiscale structures could be engineered. In-situ scattering experiment results reveal polyamorphous phase transitions occurred in the interfacial regions, which are accompanied by the evolution of medium-range order and the nanoscale heterogeneous structures during the condensation process of glassy nanoparticles under high pressure and the following heating process. Moreover, changes in the cluster connectivity resulting from repacking of the local ordering induced by pressure and temperature could be observed. The thermophysical and mechanical properties, including boson peaks, hardness, and elasticity modulus, could be changed as a function of heat-treatment parameters. Our findings would shed light on the synthesis of bulk nanostructured glassy alloys with tailorable thermodynamic and dynamical behavior as well as mechanical properties based on the understanding of metastability for polyamorphous interfacial phases. Graphical abstract: Image, graphical abstract